Exploring the Cost of Radiation Therapy Delivery for Locally Advanced Cervical Cancer in a Public and a Private Center in Latin America Using Time-Driven Activity-Based Costing - Li, B (2023)
In low- and middle-income countries (LMICs), 85% of cervical cancer diagnoses and 88% of cervical cancer deaths occur annually.1,2 The majority of presentations (with reports up to 75%)3 are locally advanced (International Federation of Gynecology and Obstetrics stages IB2 and IIBIVA) where combination external beam radiation therapy (EBRT) followed by brachytherapy is indicated for curative treatment.4 Despite large bodies of evidence that radiation therapy (RT) is effective for treating cancer, a shortage of economic investment limits its availability and contributes to global shortages.5,6 RT is generally described as a costeffective treatment, but only limited data exists about the institutional cost of combination RT in LMICs.7 Understanding treatment costs is critical for cancer capacity planning efforts, particularly in regions where radiation oncology is less understood or newly developing.